Skrining Gula Darah Puasa pada Guru dan Staf Sekolah Kelompok Bermain dan Taman Kanak-Kanak - Irawaty, Enny; Novendy, Novendy; Patricia, Dianisa; Maharani, Faadilah Indira (JPKU: Jurnal Pengabdian Kesehatan Unigal, 2025)
The 2023 Indonesian Health Survey shows a prevalence of diabetes mellitus based on blood sugar level examinations among the population aged ≥ 15 years of 11.7%, which is higher than the prevalence based on doctor diagnoses of 2.2%. Most people feel there is no need to undergo blood sugar level tests, even though blood sugar screening is an effective initial step in preventing diabetes mellitus. The busyness of teaching often prevents teachers and school staff from routinely checking their blood sugar levels. Therefore, fasting blood sugar screening activities were conducted with the aim of early detection of the onset of diabetes mellitus. The examination showed an average fasting blood sugar level of 76.22±5.88 mg/dL with a range between 67 and 89 mg/dL. These results concluded that the participants had normal fasting blood sugar levels. Screening activities like this need to be conducted regularly so that blood sugar levels can always be monitored.